Research Methodology Adopted in Developing TanSSe-L System - Kalinga, Ellen A. (Tanzania Journal of Engineering and Technology, 2019)
Research methodology is among the very important part in a research work. It is the heart which describe the activities necessary for the completion of the research work. Research methodology provides a plan of investigation considered to obtain answers to research problems and it depends on the context of application. This paper presents the research methodology adopted when developing Tanzania Secondary Schools e-Learning (TanSSe-L) system, a learning management system (LMS) which was successfully developed through customization of Moodle open source LMS. TanSSe-L system is a context centered platform for secondary schools in Tanzania. TanSSe-L system was developed using a number of methods and techniques taking into consideration open source/low cost system and the issue of sustainability, where academia, industry and Government were involved in a triple helix model. Focus group discussion in action research methodology, made secondary school stakeholders be involved in the TanSSe-L system development. Keywords: Mode 2, Model Driven Architecture (MDA), Object Oriented Approach, Open Source, Research Methodology, TanSSe-L System, Triple Helix Model.